2023
DOI: 10.1186/s12864-022-09100-8
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylome and transcriptome identified Key genes and pathways involved in Speckled Eggshell formation in aged laying hens

Abstract: Background The quality of poultry eggshells is closely related to the profitability of egg production. Eggshell speckles reflect an important quality trait that influences egg appearance and customer preference. However, the mechanism of speckle formation remains poorly understood. In this study, we systematically compared serum immune and antioxidant indices of hens laying speckled and normal eggs. Transcriptome and methylome analyses were used to elucidate the mechanism of eggshell speckle fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Caveolin-1 (CAV1) is involved in several physiological activities such as signaling, apoptosis, and lipid metabolism. It has been reported to be associated with eggshell quality and organismal aging [ 28 ]. Caveolin-2 (CAV2) and CAV1, are members of the CAV family and are involved in the formation of lipid rafts (cholesterol-rich microdomains within membranes).…”
Section: Discussionmentioning
confidence: 99%
“…Caveolin-1 (CAV1) is involved in several physiological activities such as signaling, apoptosis, and lipid metabolism. It has been reported to be associated with eggshell quality and organismal aging [ 28 ]. Caveolin-2 (CAV2) and CAV1, are members of the CAV family and are involved in the formation of lipid rafts (cholesterol-rich microdomains within membranes).…”
Section: Discussionmentioning
confidence: 99%
“…Egg weight, thin-shelled egg rate and malformed egg rate increased, while the Haugh unit, yolk color and eggshell breaking strength decreased with increasing age of hens ( Bozkurt and Tekerli, 2009 ; Ketta and Tumova, 2016 ; Molnar et al, 2016 ). It has been observed that the formation of spotted eggs is also related to the aging of laying hens ( Cheng et al, 2023 ). After the peak of egg production, the follicle numbers in laying hens markedly decline, while the number of atretic follicles increased, thus leading to a decrease in the laying rate ( Yao et al, 2020 ; Hao et al, 2021 ; Wu et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Changshun green-shell laying hen is a Chinese indigenous chicken breed with strong broodiness. Due to its strong tendency for broodiness, Changshun hen has recently become an important model to study avian incubation behaviour [22]. In the present study, we comprehensively analyzed the ovarian transcriptomes of Changshun hens at LP and BP.…”
Section: Introductionmentioning
confidence: 99%